Locus of control, marital satisfaction and marital stability among newlyweds - Sawai, Joki Perdani; Juhari, Rumaya; Kahar, Rojanah; Ismail, Zanariah; Sawai, Rezki Perdani (Southeast Asia Psychology Journal (SAPJ), 2018)
The present study examined the relationship between locus of control with marital satisfaction and marital stability in a sample of 278 newlyweds. Participants completed the Demographic Information Sheet, The Internality, Powerful Others, and Chance (IPC) Scale, Kansas Marital Satisfaction Scale (KMSS) and Marital Instability Index (MII). Correlation analysis was employed to assess relationships among the variables. Result indicated that there is a negative significant relationship between external locus of control and marital satisfaction, but there is no significant relationship between internal locus of control and marital satisfaction. Whereas, there is no significant relationship between both locus of control with marital stability. This study incongruent with past research and contributes to the new findings on locus of control.